Laboratory considerations in the assessment of 25-hydroxyvitamin D in pregnant women by automated immunoassays - Darya Ayad Khalid; Bijan Nouri; Shakhawan Abdulrahman Mustafa; Mohammad Abdi (Practical Laboratory Medicine)
Background: Because of the pathophysiological role of vitamin D in health, there is an increased interest to check the clinical status of this vitamin. Immunochemical assays are commonly employed to determine 25-hydroxyvitamin D (25 (OH) D) in clinical laboratories and its testing could be influenced by pre-analytic and analytic issues. The aim of this study was to compare the 25(OH)D results obtained from three commonly used immunoassays in pregnant women to check a possible discrepancy between tests. Material and methods: A group of 50 pregnant women who were in their third trimester were included in this study. The quantification of serum vitamin D was performed utilizing three immunochemistry-based assays including Elecsys, VIDAS and Alegria. We also involved 21 non-pregnant volunteers to clinically assess the vitamin D status in this group of people. Results: Our findings revealed a significant inconsistency between the obtained results from three assays for serum 25(OH)D. The 25(OH)D showed higher values when measured by the Elecsys assay while the VIDAS assay had lower values compared to the other immunoassays. More notably, the 25(OH)D testing in non-pregnant subjects showed consistent results in all three immunoassays. Conclusions: The results of the 25(OH)D measurements in pregnant women should be interpreted carefully due to a great inaccuracy in immunoassay testing. There is no such disagreement in non-pregnant people. Standardization of vitamin D testing in various settings is a crucial matter for clinical laboratories.